Zagrożenia procesami osuwiskowymi związane z planowaną rewitalizacją ścieżki spacerowej na Winnej Górze w Ujściu = Landslide risk associated with the planned revitalization of the walking path on the Winna Góra in Ujście - Marcin Hojan; Adam Krupa (Kazimierz Wielki University, 2015)
Hojan Marcin, Krupa Adam. Zagrożenia procesami osuwiskowymi związane z planowaną rewitalizacją ścieżki spacerowej na Winnej Górze w Ujściu = Landslide risk associated with the planned revitalization of the walking path on the Winna Góra in Ujście. Journal of Education, Health and Sport. 2015;5(12):731-743. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.47020 http://ojs.ukw.edu.pl/index.php/johs/article/view/3411 https://pbn.nauka.gov.pl/works/718158     The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport (null) 2391-8306 7 © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.12.2015. Revised 25.12.2015. Accepted: 29.12.2015.     Zagrożenia procesami osuwiskowymi związane z planowaną rewitalizacją ścieżki spacerowej na Winnej Górze w Ujściu Landslide risk associated with the planned revitalization of the walking path on the Winna Góra in Ujście   Hojan Marcin, Krupa Adam   Instytut Geografii, Uniwersytet Kazimierza Wielkiego w Bydgoszczy   Abstrakt W artykule przedstawiono zagrożenia związane z rewitalizacją ścieżki spacerowej na Winnej Górze w Ujściu. Szczególną uwagę zwrócono na opady atmosferyczne, które są ważnym czynnikiem wpływającym na zainicjowanie ruchów masowych. Wskazano istniejący stan przekształceń rzeźby na Winnej Górze oraz przeanalizowano możliwe skutki realizacji przebudowy ścieżki w pierwotnym założeniu.   Słowa kluczowe: procesy stokowe, ruchy masowe, przebudowa ścieżki.   Abstract The paper presents the risks associated with the revitalization of the walking path at Winna Góra (Vine Mountain) in Ujście. Particular attention was paid to the precipitation, which is an important factor in the initiation of mass movements. The existing state of transformation sculptures at Winna Góra and analyzed the possible effects of the implementation of the reconstruction of the path of the original premise was indicated.   Keywords: slope processes, mass movements, path reconstruction.